Marine Transportation Human Resources (HR) Based On The World Maritime Axis - Retno Anggoro; Romanda Annas Amrullah (UNIVERSITAS PAKUAN, 2023)
The desire of the newly elected President of the Republic of Indonesia Joko Widodo (Jokowi) to make Indonesia the world's maritime axis deserves appreciation. Indonesia, as an archipelagic country with a large territorial waters, great natural resource potential and a strategic location (at the crossroads of two oceans, the Indian and the Pacific), should indeed be a maritime axis. so from that related with ambition that need to wake up source power man transportation sea based on shaft maritime sector , To get there, there are a number of things that need to be done by Indonesia, including by first making Indonesia a source power man transportation sea based maritime country with a number of competencies that must be met. Currently, Indonesia is only an archipelagic country, after the implementation of UNCLOS 1982, and is trying to become an archipelagic country source power man transportation sea based maritime country for towards the world maritime pros